Efficient and stable reconstitution of the ABC transporter BmrA for solid-state NMR studies - Kunert, Britta; Gardiennet, Carole; Lacabanne, Denis; Calles-Garcia, Daniel; Falson, Pierre; Jault, Jean-Michel; Meier, Beat H.; Penin, François; Böckmann, Anja (Frontiers in Molecular Biosciences, 2014)
We present solid-state NMR sample preparation and first 2D spectra of the Bacillus subtilis ATP-binding cassette transporter BmrA, a membrane protein involved in multidrug resistance. The homodimeric 130-kDa protein is a challenge for structural characterization due to its membrane-bound nature, size, inherent flexibility and insolubility. We show that reconstitution of this protein in lipids from Bacillus subtilis at a lipid-protein ratio of 0.5 w/w allows for optimal protein insertion in lipid bilayers/membranes with respect to two central NMR requirements, a high sensitivity and sample stability over long time periods. The obtained spectra point to a well-folded protein and a highly homogenous preparation, as shown by the narrow lines and the signal dispersion typical for the expected secondary structure distribution of BmrA. This opens the way for studies of the different conformational states of the transporter in the export cycle, as well as on interactions with substrates, via chemical-shift fingerprints and sequential resonance assignments.